Spatial distribution of hypocenters of earthquakes of the Crimea-Black Sea region - Burmin, V. Y.; Shumlianska, L. O. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of a new approach to the determination of the position of earthquake hypocenters, the coordinates of all events, for which data are presented in the bulletins of the Crimean–Black Sea region for the period from 1970 to 2012, are determined. The following results were obtained: first, the majority of earthquake hypocenters lie deeper 12 km, which corresponds to 12-km border under the mountainous part of the Crimea, and almost no hypocenters, which go to the surface. Second, the distribution of earthquake hypocenters is close to the conical shape with the apex near Yalta–Alushta and the earthquake sources go to depths of 300 km. Such distribution changes a view of the geodynamic picture of the region significantly.